The Qur’an in A Christian Majority: A Case Study of Tolerance in the 29th MTQ in Saumlaki, the Moluccas, Indonesia - Didin Baharuddin; La Jamaa; Rilan Abdul Syarif (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
This paper analyses the acceptance of the majority of Christians towards implementing the 29th Qur’anic Recitation Competition (MTQ) in Maluku Province. MTQ is a form of Islamic Awakening, an event for Muslims. However, this event was held in Saumlaki, where the Muslim population is only four percent (4%). This MTQ is an anomaly where the relationship between Muslims and Christians is mutual respect, unlike in other places that are usually in conflict. Therefore, this MTQ is unique and exciting because a Christian majority carries it out, and a pastor leads the committee of the event. In this study, the acceptance of the Christian majority toward MTQ will be further examined using qualitative research and a sociological approach. The primary sources of this research are stakeholders and parties who participated in the 29th MTQ activities of Maluku Province. The data sources were determined by purposive sampling, while the secondary sources of this research were books and articles relevant to the research theme. This research shows that there is an identity transformation carried out by the majority of Christians in accepting the implementation of the MTQ, such as the use of the hijab by event organisers, who are Christians, in each segment of the competition; the use of the Catholic Center Hall as a venue for the competition, where a cross and a painting of the Virgin Mary were displayed for the Syarhil (explanation) of the Qur’an competition. This research also found a convergence in the relationship between the Muslim minority and the Christian majority. As explained, religious activities such as MTQ can be an adhesive of the relationship between Islam and Christianity and an example of religious moderation.